Legibility of neighborhood parks and its impact on social interaction in a planned residential area - Moulay, Amine; Ujang, Norsidah (Directory of Open Access Journals, 2016)
Neighbourhood parks are designed to provide opportunities for leisure and communal activities for the residents. However, studies have indicated that social interactions in these spaces are not at a satisfactory level. In the urban design context, a good public space should be legible to the observers. Legibility refers to the apparent clarity of the cityscape that directs people’s movement, pattern of activities and form of interaction in public spaces. This paper discusses park’s legibility and its impact on social interaction within a neighbourhood. The results presented are based on a questionnaire survey and a mental mapping exercise conducted with residents in the city of Putrajaya, Malaysia. The results demonstrate a strong relationship between the park’s legibility and the social interactions among the park users. A clear structure of the setting and fewer sight obstacles found within the parks influence residents’ pattern and the Intensity of outdoor activities. The findings contribute to the development of legible environments in neighbourhood park design, its positive impact on social interaction, and social bonding among the residents.